Diagnosis and prevention of rabies - Weiner, H. Richard (Compr Ther, 2001)
Over a million Americans are bitten by animals every year. Since the rabies vaccine is uniformly effective and the disease is uniformly fatal when the vaccine is not given, management decisions must be made promptly.